2010
DOI: 10.1177/104063871002200402
|View full text |Cite
|
Sign up to set email alerts
|

Avian Bornavirus is Present in Many Tissues of Psittacine Birds with Histopathologic Evidence of Proventricular Dilatation Disease

Abstract: Abstract. Proventricular dilatation disease (PDD) is a neurologic disease of psittacine birds suspected to be caused by a recently identified Avian bornavirus (ABV). In the current report, data supporting the causal association of ABV with PDD are presented. Immunohistochemistry (IHC) with rabbit polyclonal antiserum raised against ABV nucleocapsid protein was used to identify cell and organ distribution of viral antigen. The ABV antigen was most consistently detected in brain, spinal cord, adrenal gland, panc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
105
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(116 citation statements)
references
References 25 publications
(67 reference statements)
7
105
1
3
Order By: Relevance
“…2 Most sources consider the most likely method of viral transmission as fecal/oral, with virus assumed to be excreted in the feces. 1,5 However, we postulate that in fact ABV may be more likely to be spread via a urinary route. Multiple researchers have described the presence of ABV within the kidney, in Dovepress submit your manuscript | www.dovepress.com PDD-affected and ABV-infected birds via PCR and immunohistochemical staining.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…2 Most sources consider the most likely method of viral transmission as fecal/oral, with virus assumed to be excreted in the feces. 1,5 However, we postulate that in fact ABV may be more likely to be spread via a urinary route. Multiple researchers have described the presence of ABV within the kidney, in Dovepress submit your manuscript | www.dovepress.com PDD-affected and ABV-infected birds via PCR and immunohistochemical staining.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple researchers have described the presence of ABV within the kidney, in Dovepress submit your manuscript | www.dovepress.com PDD-affected and ABV-infected birds via PCR and immunohistochemical staining. 4,5,9 Indeed, some have postulated that ABV may be transmitted via the kidney or urine. 5 Avian droppings consist of a mixture of feces and urine.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, tissues in which viral RNA is detected by RT-PCR show histopathologic lesions attributable to PDD. However, a recent report also documented the same result in the cerebrum [12], and the reason for these results is unknown. Little is known about the mode of transmission of ABV, including this reported case, but previous studies have suggested horizontal transmission of the virus via oral and/or respiratory routes [13].…”
mentioning
confidence: 65%